SOSIALISASI PEMAKAIAN DAN PEMBAGIAN SARUNG TANGAN PADA MEKANIK BENGKEL ANTISIPASI TERPAPAR CEMARAN LOGAM DI DESA LALANG KABUPATEN DELI SERDANG - Dyna Grace Romatua Aruan; Maniur Arianto Siahaan; Yunita Purba (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Personal protective equipment (PPE) is very necessary when working, one of which is a workplace that requires gloves, namely workshop mechanics. One of the PPE needed by workshop mechanics is gloves. Even though it's not like masks are always required to be used to avoid exposure to heavy metals, gloves are considered to be able to protect themselves from exposure to heavy metals. Pb (Lead) is a heavy metal. Exposure to Lead (Pb) is closely related to its accumulation in body tissues which causes disruption of physiological processes both directly and indirectly at the molecular level. Lead can cause chronic effects due to lead entering through the respiratory tract, nails, skin which enters the body and digestive tract and then spreads into the blood and will inhibit heme synthesis. As a result, Pb can reduce blood Hb production which can result in the emergence of other health problems. Therefore hand protection needs to be used by people who need more protection such as tire patchers who handle motorbike repairs. Gloves have many benefits for protecting mechanics working in workshops. The main purpose of giving gloves is to protect the hands of the tire patcher when working in a workshop where the nails have the potential to be exposed to heavy metals. After distributing these gloves, it is hoped that they will be able to suppress or minimize the exposure of workshop mechanics to heavy metals, in addition to educating mechanics and workshop entrepreneurs about the importance of maintaining and protecting themselves while doing work. Keywords: Gloves, heavy metal contamination, healthy life